A robotic treadmill system to mimic overground walking training with body weight support - Kim, Jongbum; Oh, Seunghue; Jo, Yongjin; Moon, James Hyungsup; Kim, Jonghyun (Frontiers in Neurorobotics, 2023)
Body weight support overground walking training (BWSOWT) is widely used in gait rehabilitation. However, existing systems require large workspace, complex structure, and substantial installation cost for the actuator, which make those systems inappropriate for the clinical environment. The proposed system is cost/space effective, and able to mimic overground walking training with body weight support. For wide clinical use, the proposed system is based on a self-paced treadmill, and uses an optimized body weight support with frame-based two-wire mechanism. The performance of the proposed system on the measurement of anterior/posterior position, force control, and pelvic motion was evaluated. The proposed system was evaluated with 8 healthy subjects during walking training, and the results showed the feasibility of the proposed system.